Représentation de l’autre : étude des rapports entre les négriers et le peuple autochtone en Afrique au XVIIIe siècle dans le Journal de bord d’un négrier au XVIIIe de William Snelgrav - Aubain Pemangoyi Leyika (Multilinguales, 2017)
European authors’ travel stories produced regularly representations of the non-European world. Their writings are often dominated by references to unfavorable opinions about other peoples. In our study, which explores the paradigm of the encounter, we will focus on Journal de bord d’un négrier au XVIIIe siècle written by William Snelgrave. Among the authors who contributed to slave trade, there are those who explored the continents, sailed indefatigably through the seas and the oceans and lived daily with both indigenous people and slaves in the vessels. Thus, William Snelgrave, eyewitness of this commercial practice, provides in his log book abundant information on the difficulty of the transatlantic voyage and highlights the conditions imposed on Negros during this journey. This paper analyses, on the one hand, the various relation between the slave trader and the indigenous people, and those existing between the slave trader and the slaves on the other. In other words, how does Snelgrave define these interpersonal relations during slave trade? Starting from an anthropological approach, we will try to understand the functioning of the morals, the customs, and the rites described by Snelgrave to represent the Blacks in order to justify slavery, starting from the cultural practices of the indigenous peoples.